Eco-friendly synthesis of cellulose nanofibrils via mechanical-assisted ultrasonication treatment and film-forming characteristics for sustainable packaging materials - Nur Nadiah, Che Aziz; Nur Hidayah, Mat Yasin; Fatmawati, Adam; Rozaimi, Abu Samah (Wiley Online Library, 2025)
Incorporating cellulose nanofibrils (CNFs) into chitosan has shown promise for enhancing mechanical and barrier properties. However, conventional CNF production methods are time-intensive, consume significant energy, and require hazardous chemicals. This study explores the enhancement of chitosan films by incorporating CNFs, a reinforcing nanomaterial derived from microcrystalline cellulose (MCC), using mechanical-assisted ultrasonication without chemical pretreatment. The ultrasonication techniques leverage cavitation to disrupt cellulose structure and facilitate better dispersion and interaction within the matrix with higher CNF loadings (> 10% v/v). Ultrasonication effectively breaks down MCC into CNF, primarily through the formation of hydrogen bonds, leading to an increase in the crystalline index to 81.98%. Fourier transform infrared spectroscopy (FTIR) and scanning electron microscope (SEM) analyses revealed that CNFs appeared as aggregates and clusters within the chitosan matrix. Adding 20% v/v CNFs significantly enhanced the mechanical properties of the composite films, increasing the tensile strength by 39.60 MPa and the elongation at break by 106.29%. Incorporating CNFs into the chitosan film significantly improved the light transmittance and water vapor permeability properties of the composite films. Results suggest that ultrasonically extracted CNFs significantly enhance the chitosan film's structural and functional properties, making them a viable alternative for sustainable food packaging applications.